Employer branding of a global company operating in the CR - Baraćová, Kristina; Dvořáková, Zuzana, 1960-; Zajacová, Zuzana; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
Ambition of the thesis is to identify and evaluate tools that companies use to build and strengthen its employer brand in the external labour market, and internally among its employees and apply the theory of building employer brand on concrete company. The theoretical part of the thesis focuses defining brand as such, its theory and components moving through corporate brand to definition and concept of employer brand and its elements and ways of building an employer brand. The methodology of work consists of analysis of dedicated literature and papers on the topic and publicly available information about chosen company. In practical part, the thesis analyses concrete company and its employer brand using external and internal questionnaire research.
Vedoucí práce: Zuzana Dvořáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses